CONTROLLED-RELEASE FERTILIZER AFFECTS GROWTH AND YIELD OF JAPONICA RICE - P. Hou; L. Xue; S. He; Y. Zhou; G. Li; Y. Feng; L. Yang; L. Xue; 2 (Journal of Animal and Plant Sciences, 2020)
Resin-blending controlled-release fertilizer (RBB) is more consistent with the nutrient requirement of rice; the appropriate application rate though was unclear. To optimize the application rate of RBB for japonica rice in Tai-Lake region (119°54¢E, 31°17¢N), China, the effects of different application rate of first time used to given in full on grain yield. When conducted in 2015 and 2016, four application rates of RBB, i) conventional application rate (RBB1, 270 kg·ha-1), ii) reduction by 10% (RBB2, 243 kg·ha-1), iii) reduction by 20% (RBB3, 216 kg·ha-1), and iv) reduction by 30% (RBB4, 189 kg·ha-1); and the control, split application of conventional fertilizers (CN, 270 kg·ha-1), were employed. The results showed that compared with the CN treatment, a 10-30% reduction of RBB enhanced the grain yield with the yield of RBB1 treatment (9.23 t·ha-1) was the highest in 2015, when RBB3 (9.72 t·ha-1) was the highest in 2016, due to higher panicle number. The larger panicle numbers and the high LAI and photosynthetic potential after anthesis were the main reasons for the higher yield. The results indicated that the application rate of RBB could be reduced to 189-216 kg·ha-1 without affecting the grain yield.
Keywords: japonica rice; resin blending controlled-release fertilizer; application amount; yield.